The development of trust in venture capital-financing relationships : a 152.800 research thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies at Massey University - Gibbons, Anthony John (Massey University, 2004)
Venture capital-financing in New Zealand, still in its relative infancy, will come to play an increasingly important role in the economic growth of this country. Of the very limited research conducted in this area in New Zealand, the focus has been on hard data of numbers of ventures and dollars invested. Of growing interest in other industrialised markets, across all business disciplines including venture capital-financing, is the facilitative role of trust in contributing toward successful commercial outcomes. Using a qualitative approach, this thesis applies current knowledge of trust in venture capital-financing relationships to the New Zealand context and combines both survey and interview data collection methods. An adaptation of the grounded theory method is used to analyse the results. Arising from this analysis is the construction of a model illustrating the development of trust within venture capital-financing relationships. Comprehension of the model and overall research findings employs the explanatory power of a five-pillar theoretical construct of trust development comprised of agency theory, prisoner's dilemma theory, social exchange theory, procedural justice theory and interpersonal trust theory. This thesis concludes that ultimately, venture capitalists have greater control over ventures than entrepreneurs, and also that venture capital-financing relationships in New Zealand generally lack a strategic approach to the development of trust. Further, failure by venture capitalists and entrepreneurs to proactively develop trust renders their relationships prone to destruction, as predicted by existing theoretical precepts.
Keywords: New Zealand; Venture capital